2020
DOI: 10.37077/25200860.2020.33.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Broccoli Leaves (Brassica oleracea L.) Extract to Drinking Water on Eggs Production and Intestinal Microflora of Japanese Quail Coturnix japonica Temmink & Schlegel, 1849

Abstract: This study was carried out to determine the effects of adding broccoli leaves extract to drinking water on eggs production and intestinal microflora (total bacteria, lactobacilli and Escherichia coli) of breeder Japanese quails. One hundred and thirty-two 45 days-old of Japanese quails (males and females) were randomly distributed into four groups. Each group has three replicates. The groups were included: The first group was kept without any addition as the control. The extraction of broccoli leaves as 100, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In recent years, the use of medicinal plants and their derivatives in combination with feeding practices has been adopted as an alternative to antibiotics due to the multiple beneficial effects on productivity, immunity, gut development and disease resistance in poultry nutrition (Pathak et al, 2016;Oke et al, 2017;Oke, 2018;Al-Ashoor and Al-Salhie, 2020;Al-Mosawy and Al-Salhie, 2021). A large number of studies have reported that phytobiotics have antimicrobial, anti-inflammatory and transcription modulation potential (Liu, 2004;Kikusato, 2021), have beneficial effects such as inhibiting and reducing pathogenic bacteria (Alcicek et al, 2004;Alshelmani et al, 2021) and can be used as a nonantibiotic growth promoter by virtue of their effects on reducing the inflammatory process, improving gastrointestinal function, increasing growth and production performance and modulating the immune system (Saeed et al, 2020;Kairalla et al, 2022aKairalla et al, , 2022b.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of medicinal plants and their derivatives in combination with feeding practices has been adopted as an alternative to antibiotics due to the multiple beneficial effects on productivity, immunity, gut development and disease resistance in poultry nutrition (Pathak et al, 2016;Oke et al, 2017;Oke, 2018;Al-Ashoor and Al-Salhie, 2020;Al-Mosawy and Al-Salhie, 2021). A large number of studies have reported that phytobiotics have antimicrobial, anti-inflammatory and transcription modulation potential (Liu, 2004;Kikusato, 2021), have beneficial effects such as inhibiting and reducing pathogenic bacteria (Alcicek et al, 2004;Alshelmani et al, 2021) and can be used as a nonantibiotic growth promoter by virtue of their effects on reducing the inflammatory process, improving gastrointestinal function, increasing growth and production performance and modulating the immune system (Saeed et al, 2020;Kairalla et al, 2022aKairalla et al, , 2022b.…”
Section: Introductionmentioning
confidence: 99%
“…Plant extracts are used as feed additives, but It is advantageous because it increases digestibility, benefits performance, health, and immune response, and has no negative effects on the health of animals. (Oluwafemi et al, 2020;Al-Ashoor & Al-Salhie, 2020;Mahjar & Al-Salhie, 2022). Curcumin, a polyphenolic compound and one of the natural compounds extracted from turmeric roots, is the plant extract.…”
Section: Introductionmentioning
confidence: 99%
“…In ovo injection of nutrients can provide poultry producers a new way to improve hatchability and the weight of newly hatched chicks (Ohta et al, 2001). Many researchers have pointed out the importance of medicinal herbs and its extracts in stimulating growth and production and its work as antioxidants (Oke et al, 2017;Oke, 2018;Al-Ashoor & Al-Salhie, 2020;Al-Mosawy & Al-Salhie, 2021). Garlic contains a variety of antioxidants, including flavonoids and sulfur-containing compounds (Leonarduzzi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%